Penerapan Aromaterapi Lavender Pada Ny.T Dengan Postpartum Sectio Caesarea Indikasi Preeklamsia Di Ruang Delima RSUD Pasar Rebo Jakarta - Erni Ayu Wulandari; Ira Sukyati (AKPER Pasar Rebo, 2024)
Background: Preeclampsia is the onset of hypertension with proteinuria due to pregnancy after 20 weeks of pregnancy or immediately after delivery. Objective: to apply nursing care to post-sectio caesarean patients with preeclampsia who experience pain through the application of lavender aromatherapy. Research Method: descriptive method with a case study approach accompanied by the application of evidence-based practices. Results: Nursing care is carried out on the patient girl, 39 years old, with a medical diagnosis of P4A0. The results of the study obtained four nursing problems, namely acute pain associated with physical injury agents, ineffective breastfeeding associated with lack of exposure to information, risk of bleeding associated with postpartum complications, risk of infection associated with invasive procedures. The implementation was carried out by applying progressive lavender aromatherapy 5-10 minutes with a frequency of 3x/day for three days to reduce the patient's pain level. The evaluation results showed that there was a significant decrease in the pain score from a scale of 6 to a scale of 2 on the third day. Conclusion: the application of lavender aromatherapy can be applied to post sectio caesaera patients to reduce pain. Suggestion: nurses can teach the application of lavender aromatherapy to patients and their families to reduce pain.